NEW PERSPECTIVES OF GEORGIAN PHILOSOPHY IN THE LIGHT OF INTERCULTURAL THOUGHT - Zakaradze, Lali (European Scientific Journal, ESJ, 2014)
The present article analyses new perspectives of rethinking the traditional models of philosophy in the process of knowledge transformation. Problems of intercultural philosophy, its methodology and topicality in the context of modern global thought are also discussed. Special attention is given to the recent concept of intercultural philosophy (â€œcrossroadâ€) that was developed in his latest work by T. Iremadze. This concept connects systemic and historical aspects of philosophy to each other in a new way and formulates the â€œtopos of mutual understandingâ€ of different thinking traditions. The importance of the idea of â€œCaucasian Philosophyâ€ is stressed that can offer new perspectives for further research and turn the Georgian-Armenian philosophical relations into a special subject of interest.